The politics of networked learning in an age of austerity - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2014)
Networked learning has always had a connection to a set of pedagogic values and it has defined itself as linked to the development of information and communication technologies. These values and the technologies which allow for the development of contemporary networked learning mean that the field has an implicit politics. In an age of austerity what are the implications for networked learning? The development of networked learning largely coincided with the development of neo-liberal politics in advanced industrial countries and the technologies deployed to enable networked learning are largely the outcome of design and development carried out by large multi-national US based corporations. This backdrop of neo-liberal corporatism was called into question by the banking crisis of 2008 and the conversion of a private debt crisis into a sovereign debt crisis. In this process public austerity has become a dominant consideration in policy for higher education. Government has changed its relationship to higher education, most notably in the UK (focused on England), and is generally trying to both reduce overall expenditure and at the same time ensure either equivalent outputs or improved levels of output. The drive for productivity gains, a motivation for ‘more for less’, informs the hype and policy drive behind xMOOCs because they seem to offer a way to enable cheaper and wider access to higher education. This paper takes a critical look at the way austerity politics are revising the values and affecting the development of technologies for networked learning and suggests ways that researchers will need to engage with resistance to aspects of austerity politics.